A comparison of two wave models and their influence on fatigue damage in ship structures - Mao, Wengang; Prasetyo, Fredhi Agung; Ringsberg, Jonas; Osawa, Naoki (Volume 2A: Structures, Safety and Reliability, 2013)
In the maritime industry, fatigue failure is one of the most significant failure modes for ship structures. The fatigue damage in ship structures is mainly caused by the variation of wave loadings applied on ships, leading to variable structural stresses. Therefore, a reliable description of wave environments encountered during a ship’s service life is essential for accurate fatigue assessment of ship structures. Besides the wave scatter diagram provided by classification society rules, different statistical wave models have also been built up to model wave environments along arbitrary ship routes. The wave models could provide more specific wave environment for any chosen sailing routes of an individual ship. They may have the potential to be used for some practical applications, such as conceptual ship fatigue design, remaining fatigue life prediction when a ship plans to change its original trade region, and crack maintenance planning etc. Since the development of these models may be based on different sources, e.g. satellite measurements, hindcast data, buoys, etc., the reliability and consistence of wave generations from various wave models must be validated by the measured wave environments in order to be used for those practical applications. In this paper, waves generated from two different wave models, one based on hindcast data and one mainly on satellite data, are compared with measured wave environments encountered by a 2800 TEU container vessel on the North Atlantic route. These wave models are used in the calculation of the fatigue damage in the vessel. The results obtained using waves generated from the two wave models are compared with the fatigue damage calculated based on strain measurements in the ship. Recommendations for future development of the wave models and further investigation to make the applications more realistic for ship fatigue assessment are also presented.